Listening to Music Affects Diurnal Variation in Muscle Power Output - Chtourou, H.; Chaouachi, A.; Hammouda, O.; Chamari, K.; Souissi, N. (International Journal of Sports Medicine, 2012)
The purpose of this investigation was to assess the effects of listening to music while warming-up on the diurnal variations of power output during the Wingate test. 12 physical education students underwent four Wingate tests at 07:00 and 17:00 h, after 10 min of warm-up with and without listening to music. The warm-up consisted of 10 min of pedalling at a constant pace of 60 rpm against a light load of 1 kg. During the Wingate test, peak and mean power were measured. The main finding was that peak and mean power improved from morning to afternoon after no music warm-up (p<0.001 and p<0.01, respectively). These diurnal variations disappeared for mean power and persisted with an attenuated morning-evening difference (p<0.05) for peak power after music warm-up. Moreover, peak and mean power were significantly higher after music than no music warm-up during the two times of testing. Thus, as it is a legal method and an additional aid, music should be used during warm-up before performing activities requiring powerful lower limbs′ muscles contractions, especially in the morning competitive events.
Keywords: circadian rhythm; muscle power; warm-up; music